Groundwater flow and concentration of salts in agricultural soils - Coras Merino, Pablo Miguel; Ontiveros Capurata, Ronald; Diakite Diakite, Lamine (Revista Mexicana de Ciencias Agrícolas, 2018)
In rainy periods 223.8 ha in San Martín Nezahualcóyotl, Mexico State, have problems with excess moisture and high concentrations of soluble salts in the soil layers and groundwater, which vary throughout the year with fluctuations of the water table resulting in low crop yields. Isobaths planes were developed in this work, to locate areas of excessive moisture, isohypses show the directions and movement of groundwater flows and isosalinity in soil profiles. Water table oscillation was determined by analyzing 27 samples of soil and water per year over the period 2006-2011. It was found that rains in August (33 mm) and September (100.5 mm) cause the rise of the water table and excess water in the soil at 0.58 ha to 0.65 ha per mm of rainfall in 223.8 ha. In water tables over 1.51 m deep, soils had low salinity and sodicity (72.36 ha). In water tables less than 1.5 mm deep and groundwater medium to high in salts, saline soils and / or sodic soils were found, covering 59 ha (26 %) of the total area.
Keywords: rainfall; salinity; water table